Potential application of SMART II for Vibrio cholerae O1 and O139 detection in ship's ballast water. (November 2018) - Chen, Arlene; Tamburri, Mario N.; Colwell, Rita R.; Huq, Anwar
Abstract: Ballast water is used to safely stabilize and operate shipping vessels worldwide, in a multitude of aquatic settings, including inland, coastal and open oceans. However, ballast water may pose ecological, public health, and/or economic problems as it may serve as vehicles of transmission of microorganisms. Current ballast water regulations include limits of Escherichia coli, Enterococcus spp. and toxigenic Vibrio cholerae . Several United States Environmental Protection Agency approved standard operating protocols (SOPs) exist for detection of E. coli and Enterococci, yet none exists for V. cholerae . Current V. cholerae detection methods include colony blot hybridization, direct fluorescent antibody test (DFA), and/or polymerase chain reaction (PCR), which can be time consuming and difficult to perform. This study utilizes Cholera SMART II to determine its potential use in detection of V. cholerae . Validation of this method would help provide quick and accurate analysis for V. cholerae in ballast discharge waters in the field. Highlights: Transport of Vibrio cholerae by commercial vessels is a human health concern. Ballast water regulations impose limits of V. cholerae O1 and O139. Cholera SMART II is an easy test that provides rapid detection of V. cholerae . Cholera SMART II can be useful in testing of BWMS and compliance monitoring.